In Vitro Determination of Sun Protection Factor of Water Extract of Aerodramus fuciphagus from Central Kalimantan - Dita Ayulia Dwi Sandi; Eka Fitri Susiani; I Ketut Adnyana; Pratiwi Wikaningtyas (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Sunscreen is a cosmetic substance that has the ability to reflect or absorb sunlight actively. It can prevent skin irritation due to UV rays. One of the natural ingredients with a sunscreen effect is the Edible-nest swiftlet's (Aerodramus fuciphagus) nest (ESN). This study aimed to determine the value of the sun protective factor (SPF) of the ESN water extract. The ESN water extract solution with variation concentration, this is 2000, 2500, 5000, 6000, and 7000 ppm, were measured by spectrophotometric UV-Vis at wavelength 290-375 nm with 5 nm intervals to determine the value of SPF, percentage of erythema transmission (%Te), and percentage of pigmentation transmission (%Tp) of ESN water extract. The result showed that the ESN water extract's SPF values at the concentration 2000, 2500, 5000, 6000, and 7000 ppm were 7.80; 9.68; 18.75; 20.58; and 22.24. The value of %Te of each concentration were 15.60±0.19; 10.03±0.42; 1.24±0.04; 0.81±0.01 and 0.56±0.01. While the value of %Tp of each concentration was showed the sunblock category. In conclusion, the ESN water extract from Central Kalimantan at the concentration of 6000 ppm has potential in ultraviolet protection against the skin in the ultra category with sunblock category mechanism. Further, it can be developed into sunscreen cosmetics from natural ingredients.